2022
DOI: 10.3390/healthcare10030537
|View full text |Cite
|
Sign up to set email alerts
|

Dental Emergencies in an Italian Pediatric Hospital during the COVID-19 Pandemic

Abstract: Emergency rooms (ER) are largely used by patients with oral complaints, who choose the ER over private or public dental offices for oral prevention and treatment. During the COVID-19 pandemic, the activity of most dental facilities was limited, and most hospitals and ERs were dedicated to the treatment of COVID-19 patients. The present study analyzed the number of and reason for visits at the emergency room (ER) of Ospedale dei Bambini “Vittore Buzzi”, the main pediatric hospital in Milano, Italy, between 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…Emergency pedodontic procedures and underlying oral and dental needs recorded during 2020 and compared to 2019 showed disparate trends worldwide [ 5 ]. Indeed, registered admissions for emergency dental procedures proportionally increased from 2% in 2019 to 3% in 2020 at the emergency department of the Alfred I DuPont Hospital for Children in Wilmington (North Carolina, USA) [ 9 ], and similarly raise to 20.8% in South India, while decreased in 2020 compared to 2019 at Children’s Hospital Vittore Buzzi (Milan, Italy) [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency pedodontic procedures and underlying oral and dental needs recorded during 2020 and compared to 2019 showed disparate trends worldwide [ 5 ]. Indeed, registered admissions for emergency dental procedures proportionally increased from 2% in 2019 to 3% in 2020 at the emergency department of the Alfred I DuPont Hospital for Children in Wilmington (North Carolina, USA) [ 9 ], and similarly raise to 20.8% in South India, while decreased in 2020 compared to 2019 at Children’s Hospital Vittore Buzzi (Milan, Italy) [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The availability of treatment in private practices and hospitals was significantly reduced [ 16 ] as all medical resources were used to combat the then-unknown infection. In addition, during the curfew, emergency and urgent dental care were the prominent cases admitted to hospitals and facilities, which experienced an increase in admissions for early childhood caries, dental pain, facial swelling, and dental trauma worldwide, largely due to the unavailability of private and outpatient structures [ 8 , 9 , 10 , 11 , 12 ]. The restriction of dental care was justified to contain the spread of SARS-CoV-2 and to limit the consumption of personal protective equipment, which was initially in short supply.…”
Section: Discussionmentioning
confidence: 99%
“…The most common treatments offered were extractions, pulpotomies, and fillings. These studies also revealed some of the challenges and barriers to providing pediatric emergency dental care during the pandemic, such as a lack of personal protective equipment (PPE), limited access to general anesthesia, delayed referrals, and parental fear of infection [ 26 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the first spread of the COVID-19 pandemic, most public and private territorial health facilities in most countries were closed; the consequences of the suspension of routine dental care and the delay in the management of oral hygiene have led an increase in dental emergencies, especially in the pediatric population [ 38 ], which was followed by higher access to first-aid facilities for dental emergencies, especially in the most disadvantaged categories of the population.…”
Section: Discussionmentioning
confidence: 99%